(untitled) (Prilozi za orijentalnu filologiju, 2024)
Dizdarević, Dazdarević, and Dizdarlija are among the surnames that are common in Bosnia and Herzegovina. These surnames are derived from the Persian noun „dizdar“ (dizdār), which referred to the commander of a fortress during the Ottoman rule. As well as surnames, this term also generates the names of settlements as Dazdarlije, Dizdarev Potok, and Dizdaruša, specifically from the role of dizdar. This essay aims to elucidate the history of the Dizdaruša settlement, which is located close to Brčko. A certain Ali (Alija), who was an officer in the household troops of the Grand Vizier Lala Sokollu Mehmed Pasha, was the first to deliver news of the capture of the Esztergom fortress by Ottoman troops in 1605 to the Sublime Porte in Istanbul. As a reward for this, he obtained a lifetime position as the commander of the Ottoman castle of Brčko. According to the report, this appointment might have been a pivotal moment in the development of the Dizdaruša village near Brčko.